Objective Quantification of Opioid Usage After Thyroid Surgery - Agnew,Andrew (2020)
Abstract Introduction It is well established that America is in the midst of an opioid crisis with 46 people dying every day from overdoses involving prescription opioids. In the last 2 years, multiple articles have been published indicating that the amount of opioid pain medication needed after discharge from thyroid and parathyroid surgery is low. Objective To objectively examine the amount of opioid pain medication required by patients in our practice after thyroid surgery. Methods Patients were given a standardized discharge prescription of 30 pills with a combination of 7.5 mg of hydrocodone and 325 mg of acetaminophen after thyroid surgery. They were asked to log the number of pills consumed per day and the level of pain per day using the Wong-Baker faces pain scale. We used in-office pill counts to ensure accuracy of the logs. Results While reaching a similar conclusion, the present study is the first to objectively examine the quantity of opioid pain medication consumed between postoperative discharge and office follow-up. Our study objectively demonstrates that 85% of patients consumed less than 75.0 morphine milligram equivalent (MME) after thyroid surgery using in-office pill counts. Conclusion Recent multimodality anesthesia research appears promising to dramatically reduce or even eliminate the need for opioid prescriptions upon postoperative discharge.